2020
DOI: 10.1080/13548506.2020.1722315
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and physical long-term outcome in patients with a history of takotsubo cardiomyopathy or myocardial infarction - a multi-centered case control study

Abstract: Physical long-term impacts of Takotsubo Cardiomyopathy (TTC) remain controversial and an underestimation of their severity becomes increasingly evident. Even less is known about mental long-term impacts of TTC. This study aims at a better understanding of the physical and mental long-term effects of TTC in comparison to myocardial infarctions (MI). On average 5 years after disease onset, 68 TTC patients and 68 age-and sex-matched MI patients were assessed for disease-related quality of life, depression, anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
1
3
0
1
Order By: Relevance
“…These results are contrary to a recent study on resilience in TTS patients. Olliges et al found higher than normal scores of resilience in TTS patients [32]. Considering that their TTS patients were examined nearly 5 years after the TTS diagnosis, our results suggest that the resilience scores, evaluated in the acute phase, are decreased in some TTS patients.…”
Section: Discussionsupporting
confidence: 42%
“…These results are contrary to a recent study on resilience in TTS patients. Olliges et al found higher than normal scores of resilience in TTS patients [32]. Considering that their TTS patients were examined nearly 5 years after the TTS diagnosis, our results suggest that the resilience scores, evaluated in the acute phase, are decreased in some TTS patients.…”
Section: Discussionsupporting
confidence: 42%
“…Cerebral and cardiovascular events may increase the risk of developing chronic PTSD. There has been an abundance of evidence, particularly in recent years, demonstrating the enormous influence of psychological factors not only on HRQoL but also on the course of the disease and the survival chances of patients with MI, TIA or stroke [44][45][46]. These concepts and the corresponding therapeutic approaches are hardly known in the routine medical care of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although TTS is acknowledged as a transitional cardiac condition, the data on its morbidity and mortality rates is heterogeneous. While some authors have reported a higher impact of TTS on health (involving also psychiatric and neurologic disorders; Templin et al, 2015) compared to other cardiovascular syndromes, other authors have reported a similar (Olliges et al, 2020) or less severe impact (Cacciotti et al, 2012). TTS is considered as a stress-induced cardiomyopathy, associated with an inadequate management of life events (Casagrande et al, 2021), which can generate high stress levels representing the starting point of a cascade of physiological events that induce the transitive cardiac event.…”
Section: Discussionmentioning
confidence: 99%